Окремі аспекти імплементації доктрин допустимості доказів у кримінальне процесуальне законодавство України - Тесленко, І. О.; Teslenko, I. O. (Альманах права. - 2023. - Вип. 14. - С. 514-520, 2023)
У статті розглянуто положення чинного кримінального процесуального законодавства України, рішень Європейського суду з прав людини та сучасну практику судів України щодо застосування доктрин «плодів отруєного дерева» та «неминучого виявлення». Доведено, що на теперішній час перевірка доказів на їх допустимість є найважливішою гарантією охорони прав, свобод і законних інтересів учасників кримінального провадження та ухвалення законного і справедливого рішення у кримінальній справі по суті. Зазначено, що застосування доктрин або концепцій додають гнучкості кримінальному процесу у питанні визнання доказів допустимими, що забезпечує справедливість судового процесу для сторін, які беруть участь у кримінальному провадженні, певного балансу між громадськими інтересами суспільства та особи, яка притягується до кримінальної відповідальності, її прав та свобод. Зроблено висновок, що застосування як доктрини «плодів отруєного дерева», так і доктрин та концепцій, які є винятками з неї, додають гнучкості кримінальному процесу у питанні визнання доказів допустимими, що забезпечує справедливість судового процесу для обох сторін та певного балансу між громадськими інтересами суспільства та особи, яка притягується до кримінальної відповідальності, її прав та свобод.

ocedural legislation of Ukraine The author of the article researched the provisions of the current criminal procedural legislation of Ukraine, the decision of the European Court of Human Rights and the modern practice of the courts of Ukraine regarding the application of the doctrines of “fruit of the poisoned tree” and “inevitable detection”. It has been proven that at the present time, the verification of evidence for its admissibility is the most important guarantee of the protection of the rights, freedoms and legitimate interests of the participants in criminal proceedings and the adoption of a legal and fair decision in a criminal case on the merits, it is enshrined in Part 3 of Art. 62 of the Constitution of Ukraine, in particular: “the accusation cannot be based on evidence obtained illegally and on assumptions, and all doubts regarding the proven guilt of a person must be interpreted in his favor.” It was determined that in the national criminal procedural legislation the above-mentioned doctrine is actually enshrined in Part 1 of Art. 87 of the Criminal Procedure Code, in particular: “evidence obtained as a result of a significant violation of human rights and freedoms, guaranteed by the Constitution and laws of Ukraine, international treaties, the consent of which is binding by the Verkhovna Rada of Ukraine, as well as any other evidence obtained thanks to information are inadmissible , obtained as a result of a significant violation of human rights and freedoms.” The essence of the “fruits of the poisoned tree” doctrine was studied. It is emphasized that the specified doctrine and its application are not categorical, international experience contains certain exceptions to it, which are no longer focused on violations of the procedure as such, but on the consequences and impact of these violations on causing damage to individual rights or on the credibility of relevant evidence, raising doubts about their authenticity, general ensuring the justice of the judicial process, etc. As its exception, the provisions of the doctrine of “inevitable discovery” are given and analyzed. Attention is drawn to the fact that the presence of the specified doctrine as an exception to the rules provides an opportunity to maintain a balance between the interests of the accused and the interests of society, to observe more fully his rights and freedoms, and also contributes to a comprehensive consideration of the case by the court aimed at establishing the truth and preventing release guilty persons from responsibility, ensuring the inevitability of punishment. It was concluded that the application of both the doctrine of “fruits of the poisoned tree” and doctrines and concepts that are an exception to it give flexibility to the criminal process in the matter of recognizing evidence as admissible, which ensures the justice of the judicial process for both parties and a certain balance between the public interests of society and the individual, which is criminally liable, its rights and freedoms.

В статье рассмотрены положения действующего уголовного процессуального законодательства Украины, решений Европейского суда по правам человека и современной практике судов Украины по применению доктрин «плодов отравленного дерева» и «неизбежного обнаружения». Доказано, что в настоящее время проверка доказательств на их допустимость является важнейшей гарантией охраны прав, свобод и законных интересов участников уголовного производства и принятие законного и справедливого решения по уголовному делу по существу.
Some aspects of the implementation of doctrines of admissibility of evidence in the criminal procedural legislation of Ukraine
Keywords: кримінальне процесуальне законодавство; criminal procedural legislation; уголовное процессуальное законодательство; допустимість доказів; admissibility of evidence; допустимость доказательств; рішення Європейського суду з прав людини; decision of the European Court of Human Rights; решение Европейского суда по правам человека; доктрина «плодів отруєного дерева»; doctrine of "fruits of the poisoned trees"; доктрина «плодов отравленного дерева»; доктрина «неминучого виявлення»; doctrine of "inevitable discovery"; доктрина «неизбежного обнаружения»